Pengaruh Rangsangan Puting Susu Terhadap Peningkatan Kontraksi Uterus Pada Ibu Inpartu Kala Ii Di Polindes Anyelir Tunggalpager Pungging Mojokerto - Aprilia Anggraeni; Nurul Hidayah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Lack of nipple stimulation treatment is a very influential factor. Phenomenon that usually occurs in the second stage the mother is less able to push it firmly, it is more common in primigravid than multigravid mothers. The purpose of this study conducted to determine the effect of nipple stimulation to increase uterine contractions in pregnant inpartu second stage can help to increase the intensity of uterine contractions. This research was conducted in a place Polindes Carnations Tunggalpager Village District Sub Pungging Mojokerto on 23 May to 23 June 2012. This is an observational research with cross sectional design is an analytical research that studies the dynamics of the correlation between the effects of risk factors. Independentnya variable is nipple stimulation and dependentnya variable is the increase in uterine contractions. Its population is 30 persons Samples taken by 22 persons with Consecutive Sampling. Primary data collection techniques using observation sheet. Furthermore, the data analyzed, diinterpresantasikan and presented in the form of a frequency distribution table. Tested using Fisher exact test. These results indicate that almost all the respondents have increased kotraksi uterus after the nipple stimulation (86.3%) while the number of respondents after nipple stimulation did not have increased had the smallest proportion (13.7%).After the Test Fisher Exact Probability Test formula obtained 0.01 <pvalue <0.05 the results obtained 0.01 <0.022 <0.05 so Ho rejected and H1 accepted which means there is the influence of nipple stimulation to increase uterine contractions in pregnant inpartu second stage. The conclusions of this study was no effect relationship nipple stimulation to increase uterine contractions in pregnant inpartu stage II, and therefore health workers need to do nipple stimulation is to reduce the Maternal Mortality and Infant Mortality.